ANALISIS KETERSEDIAAN DAN KEBUTUHAN AIR BERSIH DI DESA DESA PURUT KECAMATAN LUMBANG KABUPATEN PROBOLINGGO - Maulana Rizal Bisri; Faradillah Saves (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The availability of potable raw water can be a difficult problem to fulfill. In the realities found in rural areas, the need for clean water is very important to ensure the quality of health, welfare, and economy of the community. Unpredictable natural factors and rapid population growth lead to an increase in the need for clean drinking water consumption. This analysis uses population data for the last 5 years requested at the village office in Purut Village, Lumbang District, Probolinggo Regency. This research will use several predetermined calculation methods so as to obtain a valid comparison for reference to the calculation of subsequent clean water needs and where from the 3 methods, 1 method was chosen, namely Geometric to be a reference for projected calculations. The purpose of this analysis is to determine the need and availability of clean water in the research location so that further accurate fulfillment planning activities can be carried out. The total clean water demand of Purut Village in 2032 according to the predicted population is 6.88 liters/second, the maximum daily demand is 8.25 liters/second, and the peak hour discharge is 11.00 liters/second. While the demand for clean water in 2032 according to the prediction of the number of each type of customer is 2.48 liters / second, the maximum daily requirement is 4.59 liters / second, and the discharge at peak hours is 6.12 liters / second. With the total demand and availability that is inversely proportional, other alternative raw water must be sought such as the addition of Pump Houses and Reservoirs in Purut Village and its surroundings so that the discharge and spring pressure can be stable and meet the need for clean water.